Generate local own source revenue: The digital business strategy of Jogja Istimewa Television - Yudistira Permana; Rizqi Azizah; Novita Wila (Journal of Innovation in Business and Economics, 2021)
This paper studies the feasible digital content business model of Jogja Istimewa Television (JITV) and Jogja Istimewa Application (JI App) under the management of the Yogyakarta Provincial Office of Communications and Informatics. Thanks to the development of digital transformation and digital content business, both are now integrated to reach a broader market since they provide unique content of Yogyakarta socio-culture and government activities. However, it needs a more advanced business model compared to the existing ones. In addition, this transformation will help The Government of Yogyakarta Province achieve its local state budget sovereignty and provide high-quality digital content for the public. We use a mix-method approach in this study by using a strict survey exploring brand awareness of JITV and JI App and focus group discussion with relevant stakeholders to achieve our objective. We find that JITV and JI App should shift their form from a unit under the Yogyakarta Provincial Office of Communications and Informatics management into an independent local public service agency (Badan Layanan Umum Daerah or BLUD). This shift is likely to be implemented since our respondents are aware of both JITV and JI App and that the relevant stakeholders in our FGD support that shift.